Designing Porous Antifouling Interfaces for High‐Power Implantable Biofuel Cell. (15th September 2021) - Wang, Lie; He, Er; Gao, Rui; Wu, Xiaotong; Zhou, Anwei; Lu, Jiang; Zhao, Tiancheng; Li, Jiaxin; Yun, Yanjing; Li, Luhe; Ye, Tingting; Jiao, Yiding; et al.
Abstract: Biofuel cells that can convert the chemical energy of biomass such as glucose into electricity are expected to continuously obtain energy from living organisms and solve bottlenecks of energy supply for implanted electronics. However, the use of biofuel cells is limited mainly by the sharp drop in performance after implanting in living organisms caused by biofouling and electrode surface inactivation. Herein, a simple and effective strategy to overcome these problems by designing a porous antifouling interface on biofuel cells, is demonstrated. It resists the biofouling from body fluid while sustaining reactant penetration, and also enhances immobilization of enzymes. As a result, the biofuel cell can maintain almost 100% performance after implanting in living organisms, and a maximal output power of 76.6 mW cm ‐3 is achieved in vivo, which is ≈ 96 times of the highest performance reported to date. This strategy is universal and can be extended to the other electronic devices such as electrochemical sensors, which presents a new avenue for developing high‐performance implanted electronics. Abstract : A porous antifouling interface is designed by combining a porous structure, high enzyme immobilization ability, and good antifouling property to produce high‐performance biofuel cells in vivo. The resulting implantable biofuel cell can maintain almost 100% performance after implanting in living organism, and a maximal output power of 76.6 mW cm –3 is achieved in vivo.